Dielectric study of Syzygium cumini Lin. at 9.85 GHz frequency. - Karhale, G A; Pawar, N P; Kalamse, G M (International Multidisciplinary Research Journal, 2012)
The values of dielectric constant ( ïƒŽï‚¢), dielectric loss (ïƒŽï‚²), relaxation time (ï´p), conductivity (ï³p) and moisture content of pulverized Syzygium cumini Lin. were measured for different packing densities at 9.85 GHz microwave frequency and different temperature (20ï‚°c, 35ï‚°c and 50ï‚°c). Experimental results on powders of different packing fractions (ï¤r) were used to obtain transformation to 100% solid bulk using correlation formulae of Landau- Lifshitz-Looyenga and Bottcher. There is fair agreement between the calculated values of dielectric parameters and the values obtained experimentally for solid bulk. This shows cohesion in the particles of spicy products under investigation.